Pathophysiological Trends During Withdrawal of Life Support: Implications for Organ Donation After Circulatory Death. Issue 12 (December 2016) - Iyer, Arjun; Chew, Hong Chee; Gao, Ling; Villanueva, Jeanette; Hicks, Mark; Doyle, Aoife; Kumarasinghe, Gayathri; Jabbour, Andrew; Jansz, Paul Cassius; Feneley, Michael P.; Harvey, Richard P.; Graham, Robert M.; et al.
Abstract : Background: Donation after circulatory death (DCD) provides an alternative pathway to deceased organ transplantation. Although clinical DCD lung, liver, and kidney transplantation are well established, transplantation of hearts retrieved from DCD donors has reached clinical translation only recently. Progress has been limited by concern regarding the viability of DCD hearts. The aim of this study was to document the pathophysiological changes that occur in the heart and circulation during withdrawal of life (WLS) support. Methods: In a porcine asphyxia model, we characterized the hemodynamic, volumetric, metabolic, biochemical, and endocrine changes after WLS for up to 40 minutes. Times to circulatory arrest and electrical asystole were recorded. Results: After WLS, there was rapid onset of profound hypoxemia resulting in acute pulmonary hypertension and right ventricular distension. Concurrently, progressive systemic hypotension occurred with a fall in left atrial pressure and little change in left ventricular volume. Mean times to circulatory arrest and electrical asystole were 8 ± 1 and 16 ± 2 minutes, respectively. Hemodynamic changes were accompanied by a rapid fall in pH, and rise in blood lactate, troponin-T, and potassium. Plasma noradrenaline and adrenaline levels rose rapidly with dramatic increases in coronary sinus levels indicative of myocardial release. Conclusions: These findings provide insight into the nature and tempo of the damaging events that occur in the heart and in particular the right ventricle during WLS, and give an indication of the limited timeframe for the implementation of potential postmortem interventions that could be applied to improve organ viability. Abstract : The authors characterize the hemodynamic, volumetric, metabolic, biochemical and endocrine changes following withdrawal of life support in a porcine asphyxia mode. It provides the indication of the limited timeframe for the implementation of potential postmortem interventions to improve organ viability.